2020
DOI: 10.37506/ijfmt.v14i3.10533
|View full text |Cite
|
Sign up to set email alerts
|

Nurses knowledge about Management Extravasation Intravenous Cytotoxic Medication At Amal National Hospital in Baghdad City

Abstract: Background: Extravasation, the unintentional leak of an anticancer agent from a vessel into the close tissues, is an uninvited and difficult problem that can lead to permanent local harms and severe disability.Objectives: To assess nurse's knowledge about management extravasation vesicant intravenous cytotoxic medication.Methodology: Descriptive design using a self-administered questionnaire was employed. At al-Amal national hospital for tumor treatment in Baghdad city from 2 nd December 2018 to 10 th February… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…Concerning years of experience, the present study indicated that slightly more than two fifth of the studied nurses had five to less than ten years' experience at oncology center. This finding agreed with study by Hussin and Ahmed, (2020) who noticed that high present of the studied nurses had five to nine years of working in the oncology unit. Another study done by Abdullah, and Rasheed, (2018) disagreed with present study, they reported that the majority of nurses had experience ranged from one to five years at oncology unit.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Concerning years of experience, the present study indicated that slightly more than two fifth of the studied nurses had five to less than ten years' experience at oncology center. This finding agreed with study by Hussin and Ahmed, (2020) who noticed that high present of the studied nurses had five to nine years of working in the oncology unit. Another study done by Abdullah, and Rasheed, (2018) disagreed with present study, they reported that the majority of nurses had experience ranged from one to five years at oncology unit.…”
Section: Resultssupporting
confidence: 93%
“…It can cause different side effects as phlebitis, hypersensitivity, infiltration, and extravasation (Bukowski, Kciuk, & Kontek, 2020). Chemotherapy extravasation is defined as the unintentional leakage of chemotherapeutic agents from the vein into surrounding tissues (Hussin, & Ahmed, 2020). It can cause pain, erythema, edema, burning, blister, and discomfort at the intravenous injection site (Taibi et al,2020).…”
Section: Introductionmentioning
confidence: 99%
“…According to the findings of this survey, 55.7% of nurses had insufficient experience (19) . In this study, 61.4% of nurses had low adherence to the clinical practice guideline, while a study done in Korea showed the guideline adherence rate was >70% (20). Moreover, in this study, 67.1% of nurses perceived more barriers to applying clinical practice guidelines to prevent chemotherapy extravasation.…”
Section: Discussionmentioning
confidence: 50%
“…More importantly, nurses, who often administer injectable drugs to patients must have correct knowledge of extravasation, observe caution during and after drug administration, and provide appropriate patient education thereafter. However, some studies on nurses' knowledge of extravasation suggest a lack of knowledge about vesicant cytotoxic 41 and noncytotoxic drugs. 42 The findings from this study reflect the actual scenario in the clinical settings and could help nurses predict possible injuries and be more vigilant while the medication is infusing, resulting in an improvement in the quality of care in infusion management.…”
Section: Nicardipine Hydrochloride (Injectable Calcium Channel Blocker)mentioning
confidence: 99%